Chlorate-based homemade explosives: A review - Horrocks, Aaron; DeTata, D.; Pitts, K.; Lewis, Simon (John Wiley & Sons, Ltd, 2023)
Chlorates and perchlorates, inorganic salts known for their potent oxidizing properties, find utility in various products such as pyrotechnics, matches, and disinfectants. Their chemical properties also make them suitable for homemade explosives, resulting in their extensive use by criminals. Hence, the forensic analysis of these compounds is vital for investigating crimes involving their utilization. A wide array of analytical techniques is available for detecting and quantifying these substances, offering forensic investigators an extensive toolkit to effectively analyze and identify chlorates and perchlorates in various samples. Recent research highlights the potential for leveraging the information obtained from analyzing these materials, including for intelligence purposes. The future of forensic analysis in this domain lies in extracting additional information, such as source attribution, through methods like chemometrics, thereby enhancing forensic intelligence capabilities. This article is categorized under: Forensic Chemistry and Trace Evidence > Explosive Analysis Forensic Chemistry and Trace Evidence > Trace Evidence Forensic Chemistry and Trace Evidence > Emerging Technologies and Methods